High‐Energy Resolution Fluorescence Detected X‐Ray Absorption Spectroscopy: A Powerful New Structural Tool in Environmental Biogeochemistry Sciences. Issue 6 (1st November 2017) - Proux, Olivier; Lahera, Eric; Del Net, William; Kieffer, Isabelle; Rovezzi, Mauro; Testemale, Denis; Irar, Mohammed; Thomas, Sara; Aguilar‐Tapia, Antonio; Bazarkina, Elena F.; Prat, Alain; Tella, Marie; et al.
Abstract : The study of the speciation of highly diluted elements by X‐ray absorption spectroscopy (XAS) is extremely challenging, especially in environmental biogeochemistry sciences. Here we present an innovative synchrotron spectroscopy technique: high‐energy resolution fluorescence detected XAS (HERFD‐XAS). With this approach, measurement of the XAS signal in fluorescence mode using a crystal analyzer spectrometer with a ∼1‐eV energy resolution helps to overcome restrictions on sample concentrations that can be typically measured with a solid‐state detector. We briefly describe the method, from both an instrumental and spectroscopic point of view, and emphasize the effects of energy resolution on the XAS measurements. We then illustrate the positive impact of this technique in terms of detection limit with two examples dealing with Ce in ecologically relevant organisms and with Hg species in natural environments. The sharp and well‐marked features of the HERFD–X‐ray absorption near‐edge structure spectra obtained enable us to determine unambiguously and with greater precision the speciation of the probed elements. This is a major technological advance, with strong benefits for the study of highly diluted elements using XAS. It also opens new possibilities to explore the speciation of a target chemical element at natural concentration levels, which is critical in the fields of environmental and biogeochemistry sciences. Core Ideas: Study shows high‐resolution spectroscopic data for an improved speciation determination. Speciation of trace elements down and below the μg g −1 level is shown. Measurements are made in vivo or at natural concentration.